Environmental Accounting Treatment in Mining Company - Wenni Anggita (Accounthink, 2019)
The environmental problem in Indonesia is an important factor to be considered considering the impact of poor environmental management is becoming more apparent nowadays. The choice of environmental problems in this study is because this problem is closest to human life. The purpose of this  resecarh to analyze environmental accounting treatment at PT. Timah (Persero) Tbk which concerns identification, recognition, measurement,  presentation and disclosure. This study which conducted use primary and secondary data. This study is decriptive study with qualitative approach which is the method which done by collecting, preparing and analyzing the obtained data descriptively.The result of this resecarh found that  environmental accounting treatment has been very effective. The financial statements of PT. Timah (Persero) Tbk has been in accordance to applicable financial accounting standards. However, the disclosure of the company’s environmental management cost still referring to the financial accounting standards (PSAK 33) which is no longer valid.